Multimaterial 3D-printed water electrolyzer with earth-abundant electrodeposited catalysts - Ambrosi, Adriano (2019)
Additive manufacturing (AM) is reaching a stage of development that enables high throughput fabrication of end products/devices. An important contribution to the advancement of this technology is given by the possibility to combine different materials into a single printing process or integrate diverse technologies for the fabrication of different components. Here we show how a prototype water electrolyzer can be fabricated using two different AM technologies, named selective laser melting and fused deposition modeling to produce the metallic components (electrodes) and the liquid/gas handling components (cells) of the electrolyzer, respectively. Both components are produced following a precise design which enables their perfect integration and assembly. The electrodes are produced in stainless steel which can be directly used for both the cathodic hydrogen evolution reaction (HER) and the anodic oxygen evolution reaction. However, we propose to introduce a simple and rapid electrochemical surface modification of the steel electrodes with more efficient earth-abundant catalysts in order to enhance the overall water splitting performance. For the HER we deposited a thin film of Ni-MoS2 composite while a NiFe double hydroxide film is deposited on the anode. Scanning electron microscopy combined with energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy are employed to characterize the electrode surface before and after the electrodeposition with the catalysts. Electrochemical testing is then used to optimize the composition of the catalysts by verifying the catalytic performance of the electrodes. As proof-of-concept, an electrochemical testing is performed with the 3D printed and assembled device.